2020
DOI: 10.1155/2020/8893305
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of 25-Hydroxycholesterol in Lipid Metabolism, Antivirus Process, Inflammatory Response, and Cell Survival

Abstract: As an essential lipid, cholesterol is of great value in keeping cell homeostasis, being the precursor of bile acid and steroid hormones, and stabilizing membrane lipid rafts. As a kind of cholesterol metabolite produced by enzymatic or radical process, oxysterols have drawn much attention in the last decades. Among which, the role of 25-hydroxycholesterol (25-HC) in cholesterol and bile acid metabolism, antivirus process, and inflammatory response has been largely disclosed. This review is aimed at revealing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 102 publications
0
24
0
Order By: Relevance
“…25-hydroxycholesterol (25-HC) is an oxysterol synthesized from cholesterol by the catalytic reaction of cholesterol-25-hydroxylase (CH25H), which is an enzyme that adds a hydroxyl group at the 25-carbone of cholesterol ( Figure 1 ) [ 16 ]. Recent studies have reported the multifunction of 25-HC in lipid metabolism, antiviral processes, inflammatory response, cell survival, and even apoptosis [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25-hydroxycholesterol (25-HC) is an oxysterol synthesized from cholesterol by the catalytic reaction of cholesterol-25-hydroxylase (CH25H), which is an enzyme that adds a hydroxyl group at the 25-carbone of cholesterol ( Figure 1 ) [ 16 ]. Recent studies have reported the multifunction of 25-HC in lipid metabolism, antiviral processes, inflammatory response, cell survival, and even apoptosis [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…25-hydroxycholesterol (25-HC) is an oxysterol synthesized from cholesterol by the catalytic reaction of cholesterol-25-hydroxylase (CH25H), which is an enzyme that adds a hydroxyl group at the 25-carbone of cholesterol ( Figure 1 ) [ 16 ]. Recent studies have reported the multifunction of 25-HC in lipid metabolism, antiviral processes, inflammatory response, cell survival, and even apoptosis [ 16 , 17 , 18 , 19 ]. In the present study, we investigated 25-HC-induced oxiapoptophagy, a type of cell death associated with oxidative stress, apoptosis, and autophagy mediated by oxysterol, and its underlying cellular signaling pathways in L929 mouse fibroblast cells.…”
Section: Introductionmentioning
confidence: 99%
“…COP metabolism in humans can be divided into two main metabolic pathways; one is to produce highly polar water-soluble products that are excreted through the metabolic cycle [57,68]. For example, 7α-HC, 25-HC, and 27-HC can be metabolized into bile acid by CY27A1 and CYP7B1 [56,[69][70][71]. The 7-hydroxylation and 27-hydroxylation of COPs by CYP27A1 and CYP7B1 are key regulatory steps in the bile acid synthesis pathway [72].…”
Section: Metabolism Of Copsmentioning
confidence: 99%
“…The endoplasmic reticulum (ER) and Golgi apparatus are the main cellular locations of CH25H, wherein CH25H catalyzes the oxidation of cholesterol to 25HC ( 1 ). CH25H is known to play multiple biological roles, especially in lipid metabolism, antiviral processes, inflammatory response, cell survival, and others ( 2 ). The enzymatic product of CH25H, 25‐hydroxycholesterol (25HC), has been previously shown to play a critical role in the blockage of cell–virus fusion in response to viral infection.…”
Section: Introductionmentioning
confidence: 99%